Long-Term Scenarios of Indonesia Power Sector to Achieve Nationally Determined Contribution (NDC) 2060 - Satria Putra Kanugrahan; Dzikri Firmansyah Hakam (Energies, 2023)
This study aims to assess the feasibility of achieving Indonesia’s net-zero emissions target by 2060 through a model of future power generation using renewable energy sources using the Low Emissions Analysis Platform (LEAP) software. There are five projected power generation scenarios in this research: the reference (REF) scenario, the conservative (CON) scenario, the moderate (MOD) scenario, the progressive (PRO) scenario, and the advanced (ADV) scenario. The availability of renewable energy technology differentiates each scenario. The ADV scenario, which utilizes nuclear power and energy storage, achieves the 100% renewable energy target by 2060 at the lowest total cost. However, the costs of CON and MOD are not significantly higher. Indonesia should decommission existing fossil fuel power plants and construct more renewable energy power plants to achieve the net-zero emissions target. Based on the simulation, biomass energy is the least favorable type of energy. Solar becomes an option only when other renewable energies are at their maximum potential capacity. Furthermore, nuclear energy and energy storage is essential for Indonesia to achieve the renewable target.